Epinotia cinereana (Haworth, 1811) bona sp., a Holarctic tortricid distinct from E. nisella (Clerck, 1759) (Lepidoptera: Tortricidae: Eucosmini) as evidenced by DNA barcodes, morphology and life history - Mutanen, Marko; Aarvik, Leif; Landry, Jean-François; Segerer, Andreas H.; Karsholt, Ole (Zootaxa, 2012)
DNA barcodes of European tortricid moths identified as Epinotia nisella (Clerck, 1759) were found to comprise two ge-netically distinct clusters. These coincided with E. nisella and E. cinereana (Haworth, 1811) (sp. rev.), the latter havingbeen considered a synonym of the former for several decades. Comparing these DNA barcodes with those of North Amer-ican Epinotia showed that both species are Holarctic. The North American Proteopteryx criddleana Kearfott, 1907 is anew junior synonym of E. cinereana (syn. nov.). The two species also show distinct differences in male and female gen-italia. North American populations of both species show moderate differences in barcodes from their respective Europeanpopulations but there are no morphological differences correlated with the intraspecific barcode clusters. Tortrix petranaHübner, 1813 is considered as a junior synonym of E. cinereana (syn. rev.). Epinotia nisella has several synonyms reflect-ing its highly variable forewing colour pattern. We discuss its variation and the status of the names associated with it. The biology of both species in Europe and North America is summarized. Adults and genitalia are illustrated.